KRITIK SOSIAL DAN BUDAYA DALAM NOVEL THE ADVENTURES OF HUCKLEBERRY FINN KARYA TWAIN MARK - Muhammad Fuad Ramadhan; Ochy Caramoy; Salma Deria Putri; Nurholis Nurholis (Cahaya Ilmu Bangsa Institute, 2024)
Abstract This study aims to discuss the theme of slavery in America as depicted in Mark Twain's novel The Adventures of Huckleberry Finn. The story of Huck and Jim reflects the racial tensions and systemic oppression present in 19th-century America. This research examines how Twain uses Huck's journey with Jim, a runaway slave, to critique the institution of slavery and challenge the moral contradictions prevalent in society at the time. Through an analysis of key episodes and character development, the study reveals the novel's critical perspective on the cruelty of slavery and the complex dynamics between race and freedom.Keywords: Slavery, Twain, Huckleberry Finn, 19th-century America, local color Abstrak Penelitin ini bertujuan untuk membahas tema perbudakan di Amerika dalam novel Mark Twain The Adventures of Huckleberry Finn. Kisah Huck dan Jim mencerminkan ketegangan rasial dan penindasan sistemik yang ada di Amerika pada abad ke-19. Studi ini meneliti bagaimana Twain menggunakan perjalanan Huck bersama Jim, seorang budak yang melarikan diri, untuk mengkritik institusi perbudakan dan menantang kontradiksi moral yang berkembang dalam masyarakat tersebut. Melalui analisis episode-episode penting dan perkembangan karakter, penelitian ini mengungkap perspektif kritis novel terhadap kekejaman perbudakan serta dinamika kompleks antara ras dan kebebasan. Kata kunci: Perbudakan, Twain, Huckleberry Finn, abad ke-18 di Amerika, local color